2009
DOI: 10.2527/jas.2008-1031
|View full text |Cite
|
Sign up to set email alerts
|

Use of a commercial probiotic supplement in meat goats1

Abstract: Sixty-three Boer crossbred goats were used in 5 separate experiments (Exp. 1 to 5) to evaluate the effects of a commercial probiotic supplement on growth performance (Exp. 1 to 4), diet digestibility (Exp. 5), carcass traits (Exp. 3), and fecal bacterial populations (Exp. 4). Goats were either fed a commercially pelleted concentrate diet and supplemented with a commercial probiotic (PRO) that had shown anecdotal positive effects on goat growth and performance according to local goat producers, or they remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 22 publications
8
59
1
1
Order By: Relevance
“…The final body weight was significantly (P<0.01) higher in calves fed with diets containing probiotics compared to control. The result of the present study was in accordance with Jaybal et al (2008) and Whitley et al (2009) those who stated that nutrient digestibility of feed was increased with adding of probiotics. The average daily weight gains were significantly (P<0.01) higher in treatment group (560.27±8.56) as compared to control group (512.28±6.52).…”
Section: Resultssupporting
confidence: 93%
“…The final body weight was significantly (P<0.01) higher in calves fed with diets containing probiotics compared to control. The result of the present study was in accordance with Jaybal et al (2008) and Whitley et al (2009) those who stated that nutrient digestibility of feed was increased with adding of probiotics. The average daily weight gains were significantly (P<0.01) higher in treatment group (560.27±8.56) as compared to control group (512.28±6.52).…”
Section: Resultssupporting
confidence: 93%
“…Animal studies have shown that mushroom enriched diet have no effect on body weight (Handayani et al, 2011). Whitley et al (2009) reported that a commercial probiotic had no effect on body weight of goats as observed in treated animals in our study. Daneshmand et al (2011) showed that supplementation of Pleurotus ostreatus had no effect on weight gain in mice during the entire experiment.…”
Section: Discussioncontrasting
confidence: 43%
“…In cattle, limited probiotic influence was observed due to the ability of ruminants to degrade most probiotics (Callaway et al, 2008). More recently, Whitley et al (2009) reported that supplementing healthy, growing meat goats' diet with probiotics conferred no consistent benefits. Further study is warranted in two key areas: (1) on the influence of probiotics on coccidia, H. Contortus and pro-inflammatory cytokines in goats and (2) Supplemental treatment for parasite infection in addition to probiotic supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical state of infection is one of the main factors responsible for kid mortality in pre-and post-weaning periods (Donkin and Boyazoglu, 2004). Using commercial probiotics, Whitley et al (2009) evaluated production performance in meat goats and reported no significant gains. However, limited studies have looked at the role probiotics play in disease progression in goats.…”
Section: Introductionmentioning
confidence: 99%